What Is Robotic Surgery and How Does AI Enhance It? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Robotic surgery has emerged as a transformative force in modern medicine, offering unprecedented precision and control to surgeons. This technology, once the...
Keywords: AI in Surgery and Robotics; Robotic; Surgery; Enhance; Artificial Intelligence